2023
DOI: 10.7759/cureus.34805
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Missed Injuries in Multiple Trauma Patients at a Level-1 Trauma Center in Saudi Arabia

Abstract: BackgroundMissed injuries are defined as injuries neither detected in the emergency department (ED) nor after admission to the hospital. The objective of this research was to identify missed injury rates, contributing factors, and clinical outcomes. MethodsA total of 657 trauma patients' records were retrospectively reviewed after admission to King Abdulaziz Medical City (KAMC) during the period from January 2016 to December 2018. Patients' demographic characteristics, presence of a missed injury, and Glasgow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
0
1
Order By: Relevance
“…Added to the knowledge data obtained from respondents, it was revealed that players with diverse joining backgrounds tend to stretch when they start to feel neck pain; this is done to ensure their comfort is maintained. This finding differs from previous research, where the joining period affects amateur players who have just joined, having a higher risk level for musculoskeletal disorders than players who have joined for 10 years (Fathuldeen et al, 2023).…”
Section: Discussioncontrasting
confidence: 99%
“…Added to the knowledge data obtained from respondents, it was revealed that players with diverse joining backgrounds tend to stretch when they start to feel neck pain; this is done to ensure their comfort is maintained. This finding differs from previous research, where the joining period affects amateur players who have just joined, having a higher risk level for musculoskeletal disorders than players who have joined for 10 years (Fathuldeen et al, 2023).…”
Section: Discussioncontrasting
confidence: 99%